2022
DOI: 10.3390/coatings12121857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coating Process on Properties of Two-Component Waterborne Polyurethane Coatings for Wood

Abstract: Acrylic acid has good environmental weather resistance, water resistance, alcohol resistance, dirt resistance, and other properties. An acrylic acid dispersion with a core–shell structure was prepared and reacted with a polyisocyanate-type curing agent to prepare a waterborne polyurethane topcoat suitable for wood. The prepared two-component polyurethane topcoat was used in combination with a waterborne primer and a waterborne sealing primer and applied to Pine (Pinus strobus) boards to carry out gloss, wear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The analysis of the coating’s optical characteristics revealed that a coating with a high gloss level makes substrate flaws obvious. The requirements for the flatness and roughness uniformity of the substrate are relatively high [ 45 , 46 ]. As a protective coating, it is often subject to friction, impact, tension, and other forces, so the coating film is required to have necessary mechanical properties [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the coating’s optical characteristics revealed that a coating with a high gloss level makes substrate flaws obvious. The requirements for the flatness and roughness uniformity of the substrate are relatively high [ 45 , 46 ]. As a protective coating, it is often subject to friction, impact, tension, and other forces, so the coating film is required to have necessary mechanical properties [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, waterborne coatings cannot adapt to the deformation of wood caused by shrinkage when dry and later expansion, and their toughness is far lower than that of typical organic coatings. They are more prone to cracking after drying, reducing the service life of the wood [7,8]. Microcapsule technology aims to use natural or synthetic polymer compounds to form a continuous film (wall material) to wrap a material (core material), so that the chemical properties and functions of the core material are not affected and can be protected by the wall material.…”
Section: Introductionmentioning
confidence: 99%
“…By encapsulating the core material of repair agent into microcapsules and adding them to a waterborne coating, the coatings can be self-healing. This extends a service life of the coating, which in turn better protects the wood substrate [7][8][9]. For example, the self-healing shellac microcapsules are incorporated into the coating.…”
Section: Introductionmentioning
confidence: 99%